Modified surgical safety checklist (mSSC)- a must to avoid disaster in neurosurgical procedures! - Thapa, Amit; KC, Bidur; Shakya, Bikram; Bhurtyal, Shusma (Nepal Journal of Neuroscience, 2017)
The World Health Organization (WHO) introduced surgical safety checklist (SSC) as a part of Second Global Patient Safety Challenge: Safe Surgery Saves Lives to address the safety of surgical care. Althoughfound to be benefi cial for general surgical patient, we introduced certain modification to suit neurosurgical patients and hereby present our experience with the modified checklist.We introduced the modified SSC in July 2012 for neurosurgical purpose after we identified minor but common errors in carefully audited 100 patients in our operating theatre. Modification included checklists in pre procedure room, during sign in enquiring for pulse oximeter (for local anesthetic procedures) and lastly during sign out an elaborated list of items to guarantee safe transfer of the patients. Nurses and doctors were trained and SSC was methodically administered.Outcome as number of complications was evaluated and graded according to no harm, low harm, moderated harm, severe harm and death. During last 5 years (July 2012 to June 2017), 1310 patients undergoing surgical procedures in neurosurgical theatre at KMCTH were studied. Modified SSC was used in both routine (50.5%) and emergency cases (49.5%), of which compliance was 80% and 55% respectively. Poor compliance was due to ignorance of its use, emergency nature of procedure, change of staff. Completeness of mSSC was found in 70% cases with most left out part of mSSC was during signing out (i.e during transfer of patients). Use of mSSC identified many common but minor negligent acts on part of doctors, nurses and OR technicians which could be rectified in time and hence avoided any major mishaps. Age of the patients ranged from newborn to 98 year old. There were no major mishaps including death on table events. Despite confirming during mSSC checklist, machine failure occurred in 10 cases (0.8%) which were of low harm category. The total time taken for performing and filling the checklist took roughly 7 minutes.We modified WHO surgical safety checklist to include post operative transfer out to recovery room and used it in both routine and emergency procedures. This has helped us to avoid major mishaps during and after the neurosurgical procedures. We recommend stringent use of SSC in all neurosurgical centre and advise suitable local modifications according to prevailing conditions for special procedures or locations.Nepal Journal of Neuroscience, Volume 14, Number 3, 2017, page: 7-12